2016
DOI: 10.11604/pamj.2016.25.82.4151
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and comorbidities of autism among children referred to the outpatient clinics for neurodevelopmental disorders

Abstract: IntroductionAutism spectrum disorders (ASD) is a neurodevelopmental disorder that has been rarely diagnosed in Sub-Saharan Africa. Although a proportion of children do present features of ASD in the Democratic Republic of Congo (DRC), little is known about it prevalence. Often, the co-morbidities constitute the upfront symptoms and therefore may it recognition and management difficult, aggravating as such the prognosis. The present study therefore aimed at studying the clinical profile of autism spectrum disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
30
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 28 publications
5
30
0
3
Order By: Relevance
“…Randall et al 2016), and these tend to be higher than those estimated in low-income countries (Elsabbagh et al 2012). This could suggest that there are significant numbers of autistic people in other nations, including African and Asian nations, who are not recognised by or receiving support from medical or educational systems (Hossain et al 2017;Mpaka et al 2016); alternatively, there may be lifestyle factors in more developed nations which lead to greater incidence of autism.…”
Section: Autism Diagnosis and Prevalencementioning
confidence: 99%
“…Randall et al 2016), and these tend to be higher than those estimated in low-income countries (Elsabbagh et al 2012). This could suggest that there are significant numbers of autistic people in other nations, including African and Asian nations, who are not recognised by or receiving support from medical or educational systems (Hossain et al 2017;Mpaka et al 2016); alternatively, there may be lifestyle factors in more developed nations which lead to greater incidence of autism.…”
Section: Autism Diagnosis and Prevalencementioning
confidence: 99%
“…The other pitfall was that in our method we interrogated each disease term one by one, as if they were independent diseases. However, several of the diseases had high comorbidities, as previously reported (Blacher & Kasari, 2016;Lo-Castro & Curatolo, 2014;Mpaka et al, 2016). In fact, the gene panel used in this CAGI challenge was originally designed to study the genetics underlying the comorbidities of intellectual disability and autism spectrum disorders.…”
Section: Postchallenge Analyses: Comparison With the State-of-the-amentioning
confidence: 92%
“…Many neurodevelopmental disorders have profound heritability, highly heterogeneous genetic causes, and significant comorbidities (Blacher & Kasari, ; Brainstorm et al, ; Lo‐Castro & Curatolo, ). For instance, researchers have found that intellectual disability and epilepsy can have larger than 70% co‐occurrence rates with autism spectrum disorders in some population (Mpaka et al, ). With prior knowledge of such disorders, the Padua Diagnostic Laboratory designed a gene panel primarily for studying the genetic mechanisms underlying the comorbidity of intellectual and autism spectrum disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otro lado, la discapacidad intelectual implica la presencia de deficiencias en habilidades mentales generales que involucran el funcionamiento cognitivo y adaptativo (APA, 2014). Esta última y su comorbilidad con TEA puede ser estimada entre un 18 y 40 % (Mbeya Mpaka et al, 2016;Tonnsen et al, 2016). Al manifestarse en conjunto, el desafío terapéutico es más complejo, porque suele estar asociado a elevados índice de comportamientos restrictivos y repetitivos (incluyendo autolesiones), y mayores dificultades a nivel comunicacional (Fusar-Poli et al, 2017;Oliver, Licencce y Richards, 2017;Tonnsen et al, 2016).…”
unclassified